2011
DOI: 10.1063/1.3582084
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear beam generated plasma waves as a source for enhanced plasma and ion acoustic lines

Abstract: Observations by, for instance, the EISCAT Svalbard Radar (ESR) demonstrate that the symmetry of the naturally occurring ion line in the polar ionosphere can be broken by an enhanced, nonthermal, level of fluctuations (naturally enhanced ion-acoustic lines, NEIALs). It was in many cases found that the entire ion spectrum can be distorted, also with the appearance of a third line, corresponding to a propagation velocity significantly slower than the ion acoustic sound speed. It has been argued that selective dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The irregular Langmuir envelope modulation has been clearly reproduced in a series of particle-in-cell (PIC) simulations of electron-beam-plasma interaction (Omura et al, 1996;Muschietti et al, 1996;Matsukiyo et al, 2004;Usui et al, 2005) and in electrostatic Vlasov simulations (Umeda, 2006;Silin et al, 2007;Daldorff et al, 2011;Sauer and Sydora, 2012), but the simulations do not reveal the physical nature of the phenomenon. Coherent modulation and the associated double peak have as yet not been explained, neither theoretically nor in terms of numerical simulations.…”
Section: Introductionmentioning
confidence: 98%
“…The irregular Langmuir envelope modulation has been clearly reproduced in a series of particle-in-cell (PIC) simulations of electron-beam-plasma interaction (Omura et al, 1996;Muschietti et al, 1996;Matsukiyo et al, 2004;Usui et al, 2005) and in electrostatic Vlasov simulations (Umeda, 2006;Silin et al, 2007;Daldorff et al, 2011;Sauer and Sydora, 2012), but the simulations do not reveal the physical nature of the phenomenon. Coherent modulation and the associated double peak have as yet not been explained, neither theoretically nor in terms of numerical simulations.…”
Section: Introductionmentioning
confidence: 98%
“…Plasma wave generation may also modify streaming non-thermal electron populations in flaring coronal loops 14,15 . In the ionosphere, plasma a) Electronic mail: h.ratcliffe@warwick.ac.uk wave interactions may lead to naturally enhanced ionacoustic lines seen in radar observations 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Vlasov simulations of weak beam-plasma interactions are less common. For example, Daldorff et al 17 considered ionospheric electron beams modifying ion-acoustic lines, but were forced to use unphysical pa-rameters such as a 1% beam density for computational reasons, altering the processes of Langmuir wave generation and scattering. Henri et al 23 considered finite Langmuir wave-packets and concluded that for sufficiently fast wave growth ion-sound wave damping could be overcome even in plasma of equal ion and electron temperature, and resonant wave-wave interactions would proceed as usual.…”
Section: Introductionmentioning
confidence: 99%
“…2005; Baumgärtel, 2013) and electrostatic Vlasov simulations (Umeda, 2006;Silin et al, 2007;Umeda, 2007;Umeda and Ito, 2008;Daldorff et al, 2011;Sauer and Sydora, 2012). Studies which include ion dynamics (in some cases with a reduced proton-to-electron mass ratio) show clearly that the heavy particles indeed contribute to the evolution of the instability.…”
Section: K Baumgärtel: Ion Dynamics In Electron Beam-plasma Interactionmentioning
confidence: 99%